Механізм захисної дії амфіфільних сполук в умовах гіпертонічного гемолізу еритроцитів - Орлова, Н.В.; Шпакова, Н.М. (Фізіологічний журнал. 2006; 52 (5): 55–61, 2006)
Antihemolytic effect of various amphiphilic compounds under conditions of red blood cell hypertonic hemolysis at different temperatures (0 and 37 °C) and cell exposure to diamide was investigated. The level of maximum antihemolytic activity and values of efficient concentrations for all studied substances were lower at 0°C if compared with 37°C. Exposure of erythrocytes to diamide (5 and 10 mmol/l) did not change cell sensibility to hypertonic medium. There has been demonstrated a temperature-dependent decrease in the efficiency of studied substances under hypertonic hemolysis of erythrocytes exposed to 10 mmol/l diamide. Found reduction in efficiency of amphiphiles at low temperature and at high concentration of diamide was probably caused by similar changes of structural and dynamic state of erythrocyte membrane.
TO THE QUESTION ABOUT MECHANISM OF PROTECTIVE EFFECT OF AMPHIPHILIC COMPOUNDS UNDER HYPERTONIC HEMOLYSIS OF ERYTHROCYTES
Орлова НВ, Шпакова НМ. Механізм захисної дії амфіфільних сполук в умовах гіпертонічного гемолізу еритроцитів. Фізіологічний журнал. 2006; 52 (5): 55–61
Keywords: еритроцити людини; гіпертонічний шок; амфіфільні речовини